Plan in 2-D, execute in 3-D: An augmented reality solution for cup placement in total hip arthroplasty - Fotouhi, Javad; Alexander, Clayton P.; Unberath, Mathias; Taylor, Giacomo; Lee, Sing Chun; Fuerst, Bernhard; Johnson, Alex; Osgood, Greg; Taylor, Russell H.; Khanuja, Harpal; Armand, Mehran; Navab, Nassir (Journal of Medical Imaging, 2018)
Reproducibly achieving proper implant alignment is a critical step in total hip arthroplasty procedures that has been shown to substantially affect patient outcome. In current practice, correct alignment of the acetabular cup is verified in C-arm x-ray images that are acquired in an anterior-posterior (AP) view. Favorable surgical outcome is, therefore, heavily dependent on the surgeon's experience in understanding the 3-D orientation of a hemispheric implant from 2-D AP projection images. This work proposes an easy to use intraoperative component planning system based on two C-arm x-ray images that are combined with 3-D augmented reality (AR) visualization that simplifies impactor and cup placement according to the planning by providing a real-time RGBD data overlay. We evaluate the feasibility of our system in a user study comprising four orthopedic surgeons at the Johns Hopkins Hospital and report errors in translation, anteversion, and abduction as low as 1.98 mm, 1.10 deg, and 0.53 deg, respectively. The promising performance of this AR solution shows that deploying this system could eliminate the need for excessive radiation, simplify the intervention, and enable reproducibly accurate placement of acetabular implants.
CRIS-Team Scopus Importer:2023-03-08
Keywords: augmented reality; intraoperative planning; RGBD camera; total hip arthroplasty.; x-ray